THE ROLE OF LEADERSHIP AND ORGANIZATIONAL CULTURE IN MEDICAL ERROR MANAGEMENT: A COMPREHENSIVE LITERATURE REVIEW - Kiridjiievska, Lidija Veljanovska; Borota Popovska, Mirjana; Topuzovska Latkovikj, Marija; Drakulevski, Ljubomir (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
This paper highlights the serious implications of medical errors, ranging from minor oversights to critical errors, on patient outcomes, institutional reputation, and the overall integrity of health care systems. Recognizing the enormous number of medical errors, the review considers the roles that leadership and organizational culture play in the management of such errors, placing them as focal points in scientific research and operational focus. Leadership in healthcare organizations is emerging as a central theme, with leaders playing a key role in shaping policy, setting standards, and fostering an environment that prioritizes patient safety above all else. These leaders must champion error prevention, ensuring it is embedded in the organization's ethos and operational strategies. Furthermore, fostering a culture of open communication where frontline health workers feel empowered to report errors without fear of retribution is essential to identifying systemic vulnerabilities and implementing corrective measures. Equally important is the organizational culture in healthcare facilities. A culture that prioritizes patient safety and promotes non-punitive responses to errors is vital to mitigating them. This includes creating an environment that encourages reporting errors and sees it as an opportunity to learn and improve rather than spur to punish. In synthesizing findings from the literature, this review aims to provide a comprehensive understanding of leadership strategies and organizational culture critical to mitigating medical errors.  Ultimately it aims to contributing to the advancement of healthcare systems that place paramount importance on patient safety and significantly reduce medical errors. Keywords: Medical errors, leadership strategies, organizational culture, patient safety.